2019
DOI: 10.1128/jvi.00543-19
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Fitness of Mexican H7N3 Highly Pathogenic Avian Influenza Virus in Mallards after Circulating in Chickens

Abstract: Outbreaks of highly pathogenic avian influenza (HPAI) virus subtype H7N3 have been occurring in commercial chickens in Mexico since its first introduction in 2012. In order to determine changes in virus pathogenicity and adaptation in avian species, three H7N3 HPAI viruses from 2012, 2015, and 2016 were evaluated in chickens and mallards. All three viruses caused high mortality in chickens when given at medium to high doses and replicated similarly. No mortality or clinical signs and similar infectivity were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…H7N3 viruses isolated from Mexico have been further analyzed for protection in chickens and for their fitness in chickens and mallards. Variations in protection and fitness have been found between viruses isolated from different years as shown in recent reports [7,8].…”
Section: Introductionmentioning
confidence: 77%
“…H7N3 viruses isolated from Mexico have been further analyzed for protection in chickens and for their fitness in chickens and mallards. Variations in protection and fitness have been found between viruses isolated from different years as shown in recent reports [7,8].…”
Section: Introductionmentioning
confidence: 77%
“…The layer chickens used in this study were 35-week-old and had brown feathers, which are recognized as exhibiting reduced virulence against HPAI 24 . Additionally, the pathogenesis of avian influenza might be showed in the difference of susceptibility depending on age in various reports [25][26][27][28][29] although it was recently reported that age is not a determinant factor in susceptibility to H5N2 HPAIv 30 . Our results are not consistent with a previous study showing that commercial chickens experienced less immunization than laboratory chickens due to maternal antibodies, immunosuppressive viruses, and the use of a lower vaccine dose 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of sequences used for phylogenetic analysis are as follow: PB2 (n = 393), PB1 (n = 350), PA (n = 376), HA (n = 372), NP (= 358), NA (n = 398), M (n = 343), and NS (n = 305). In addition to the viruses sequenced in this study, full genome sequences of 18 viruses available in the Influenza Research Database, including viruses previously sequenced in our laboratory were retrieved (access date: July 2018) for full genome analysis of the Mexican H7N3 viruses from 2012 to 2017 [15]. For the estimations of substitution rate using the Bayesian analyses, the wild bird AI sequences clustering with the initial Mexican H7N3 sequences were extracted from the Maximum-likelihood phylogenetic trees, with bootstrap value (n > 70).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we demonstrated phenotypic and antigenic changes in recent Mexican lineage H7N3 viruses. A H7N3 HPAI virus isolated in 2016 was less adapted to mallards than the index virus from 2012, and increase in N-glycosylation on the HA was associated with escape of a field virus from a older vaccine [15, 16]. However, detailed information on the evolutionary history of the Mexican lineage H7N3 HPAI virus is lacking.…”
Section: Introductionmentioning
confidence: 99%